Decision Support System for Selecting the Best Smartphone Using the Multi Attribute Utility Theory (MAUT) Method at Sinar Mas Selluler Kudus - Arina Fawaida; Noor Latifah; Yudie Irawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The increasing variety of smartphone products with different specifications and prices makes the selection process more difficult for customers and often results in subjective recommendations from sales personnel. This study aims to develop a web-based Decision Support System (DSS) for smartphone selection at Sinar Mas Selluler Kudus using the Multi Attribute Utility Theory (MAUT) method. The system evaluates smartphone alternatives based on five criteria: Random Access Memory (RAM), Internal Storage, Screen Size, Battery Capacity, and Price. The research employed the System Development Life Cycle (SDLC) approach, including planning, analysis, design, implementation, and testing. The MAUT method was applied through criteria weighting, utility normalization, preference value calculation, and ranking to generate objective recommendations. The developed system was functionally validated using Black Box Testing to ensure that all system features operated according to the specified functional requirements. The developed system successfully automated the evaluation process, reduced subjective decision-making, and improved the efficiency of smartphone selection. The calculation results showed that Huawei (A3) achieved the highest preference value of 0.7215, indicating that it is the most suitable smartphone alternative according to the predefined criteria and weights. The implementation results demonstrate that the proposed system can assist sales personnel in providing objective recommendations while helping customers compare smartphone alternatives more efficiently based on their preferences and budget constraints. Therefore, the proposed system provides accurate, transparent, and consistent recommendations to support customers and sales personnel in making better purchasing decisions.